Interdecadal Pacific Oscillation in Northern Greenland Dust Concentration Variability During the Last 400 Years. Issue 24 (23rd December 2022) - Rimbu, N.; Ionita, M.; Lohmann, G.
Abstract: Statistical analysis of reanalysis and observed data reveals that high dust surface mass concentration in northern Greenland is associated with a Pacific Decadal Oscillation like pattern in its negative phase in the North Pacific as well as with La Niña conditions in the tropical Pacific region. The sea surface temperature anomalies in the Pacific realm resemble the Interdecadal Pacific Oscillation (IPO). The associated atmospheric circulation pattern, in the form of a wave‐train from the North Pacific to the Eurasian continent, favors enhanced dust uptake and transport toward the northern Greenland. Similar patterns are associated with a low‐resolution stacked record of five Ca 2+ ice cores, that is, ngt03C93.2 (B16), ngt14C93.2 (B18), ngt27C94.2 (B21), GISP2−B, and NEEM‐2011‐S1, from northern Greenland, a proxy for regional dust concentration, during the last 400 years. We argue that northern Greenland ice core dust records could be used as proxies for the IPO and related teleconnections. Plain Language Summary: Observational and modeling studies show that, during the observational period, interannual to multidecadal dust concentration variability is related to the dominant modes of climate variability at these time scales. Here we show that Interdecadal Pacific Oscillation (IPO) signal is robustly recorded in low‐resolution dust ice core records from the northern Greenland during the last 400 years. We argue that northern Greenland ice core dust records could be used to put the IPO activity and related teleconnections during the observational period into a long‐term perspective. Key Points: Northern Greenland dust concentration variability shows global teleconnections during the instrumental period The most stable pattern associated with northern Greenland ice core dust variability is the Interdecadal Pacific Oscillation (IPO) Northern Greenland ice core dust records could be used as a complementary source of information about IPO during the past